Overlapping frontoparietal networks in response to oculomotion and traumatic autobiographical memory retrieval: implications for eye movement desensitization and reprocessing. Issue 1 (31st December 2019) - Harricharan, Sherain; McKinnon, Margaret C.; Tursich, Mischa; Densmore, Maria; Frewen, Paul; Théberge, Jean; van der Kolk, Bessel; Lanius, Ruth A.
ABSTRACT: Background : Oculomotor movements have been shown to aid in the retrieval of episodic memories, serving as sensory cues that engage frontoparietal brain regions to reconstruct visuospatial details of a memory. Frontoparietal brain regions not only are involved in oculomotion, but also mediate, in part, the retrieval of autobiographical episodic memories and assist in emotion regulation. Objective : We sought to investigate how oculomotion influences retrieval of traumatic memories by examining patterns of frontoparietal brain activation during autobiographical memory retrieval in post-traumatic stress disorder (PTSD) and in healthy controls. Method : Thirty-nine participants (controls, n  = 19; PTSD, n  = 20) recollected both neutral and traumatic/stressful autobiographical memories while cued simultaneously by horizontal and vertical oculomotor stimuli. The frontal (FEF) and supplementary (SEF) eye fields were used as seed regions for psychophysiological interaction analyses in SPM12. Results : As compared to controls, upon retrieval of a traumatic/stressful memory while also performing simultaneous horizontal eye movements, PTSD showed: i) increased SEF and FEF connectivity with the right dorsolateral prefrontal cortex, ii) increased SEF connectivity with the right dorsomedial prefrontal cortex, and iii) increased SEF connectivity with the right anterior insula. By contrast, as compared to PTSD, upon retrieval of a traumatic/stressful memory while also performing simultaneous horizontal eye movements, controls showed: i) increased FEF connectivity with the right posterior insula and ii) increased SEF connectivity with the precuneus. Conclusions : These findings provide a neurobiological account for how oculomotion may influence the frontoparietal cortical representation of traumatic memories. Implications for eye movement desensitization and reprocessing are discussed. HIGHLIGHTS: Traumatic/stressful memory retrieval while performing horizontal eye movements engages frontoparietal regions involved in autobiographical memory retrieval and emotion regulation that show further connectivity with the right frontal and supplementary eye fields. Dissociation may compromise the oculomotor frontoparietal network's ability to recruit the right dorsolateral prefrontal cortex for use in top–down emotion regulation. Oculomotion may influence the frontoparietal cortical representation of traumatic memories. These findings may have implications for eye movement desensitization and reprocessing therapies.